Analysis The Quality Of Tourism Services And Facilities In Increasing The Happiness Of The Visiting Community (Study On Kayangan Hill Tourism, Renah Kayu Embun Village, Sungai Penuh City, Jambi Province) - Wahyu Arsyad; Aldri Frinaldi (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Bukit Khayangan is the name of a flagship tour of Sungai Penuh City which is managed by the Department of Culture and Tourism of Sungai Penuh City. However, problems are still found because there are visitors who are disappointed because Bukit Khayangan Tourism is not well maintained, such as garbage scattered about because the trash can is not yet available. In addition, there are no guide officers who directly serve tourists. Tourist facilities such as tourist huts that were built on the strategic side of this tour are feared that the roof will fall on visitors who are sitting in the hut. Then the unavailability of lodging around the tour. This study uses a quantitative method with an associative approach whose aim is to determine the effect of the independent variable (Quality of Service and Tourism Facilities) on the dependent variable (Community Happiness). The population in this study were visitors to Bukit Khayangan Tourism in 2020, amounting to 15,512 people. The sample in the study was determined by the Taro Yamane formula and an error rate of 10%, so that a sample of 100 respondents was obtained. Then from the sample, using the Proportional Random Sampling technique, if the technique is not sufficient in the number of samples, it will be continued with the Accidental Sampling technique. by 26.6% ; tourism facilities on the happiness of the community from the R Square value of 0.103, which is 10.3%. And simultaneously, the two dependent variables on people's happiness from the Adjusted R Square value of 0.347, which is 34.7%. From the results of data processing, it is proven that the people who visit Bukit Khayangan Tourism are happy with the services provided by the tour manager and also the tourist facilities provided by the Sungai Penuh City Culture and Tourism Office.